2015
DOI: 10.1016/j.clnu.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Impact of nasogastric tubes on swallowing physiology in older, healthy subjects: A randomized controlled crossover trial

Abstract: Background & Aims:The presence of a nasogastric tube (NGT) affects swallowing physiology but not function in healthy young adults. The swallowing mechanism changes with increasing age, therefore the impact of a NGT on swallowing in elderly individuals is likely to be different but is not yet known. The aims of this study were to determine the effects of NGTs of different diameter on (1) airway penetration-aspiration, (2) pharyngeal residue, and (3) pharyngeal transit, in older healthy subjects. Methods:Randomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…A more recent trial in older healthy subjects concluded that the presence of an NGT increases airway penetration‐aspiration and pharyngeal residue and prolongs transit through the pharynx in older healthy individuals. Consideration of the impact of an NGT on swallowing during concurrent oral and enteral feeding is recommended, with further systematic investigation required in elderly patients recovering from critical illness .…”
Section: Myths/unfounded Practices and Evidence For Appropriate Practicementioning
confidence: 99%
“…A more recent trial in older healthy subjects concluded that the presence of an NGT increases airway penetration‐aspiration and pharyngeal residue and prolongs transit through the pharynx in older healthy individuals. Consideration of the impact of an NGT on swallowing during concurrent oral and enteral feeding is recommended, with further systematic investigation required in elderly patients recovering from critical illness .…”
Section: Myths/unfounded Practices and Evidence For Appropriate Practicementioning
confidence: 99%
“…Tubes often bend and coil in the pyriform sinus and arytenoid cartilage during insertion [17, 18]. In addition, physiological or pathological variations of a patient's functional anatomy can predispose to prolonged procedure or misplacement [1921].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of aspiration pneumonia in tube‐fed patients is reported between 7% and 62%, with a mortality rate of 17% to 62% . Among various tube‐feeding techniques, nasogastric tube (NGT) feeding has the added disadvantage of disturbing the protective mechanism of the lower esophageal sphincter (LES) and upper esophageal sphincter (UES) against reflux …”
Section: Introductionmentioning
confidence: 99%
“…17 Among various tube-feeding techniques, nasogastric tube (NGT) feeding has the added disadvantage of disturbing the protective mechanism of the lower esophageal sphincter (LES) and upper esophageal sphincter (UES) against reflux. [18][19][20] The main mechanism of gastroesophageal reflux in this patient population is likely related to the increased number of inappropriate transient lower esophageal sphincter relaxations in the setting of increased gastric volume/content. After entry of gastric content into the esophagus, there remain two mechanisms for containing the refluxate in the esophagus and preventing its entrance into the pharynx, which is a prerequisite for aspiration.…”
Section: Introductionmentioning
confidence: 99%